2019
DOI: 10.4136/ambi-agua.2289
|View full text |Cite
|
Sign up to set email alerts
|

Flow distribution and trends in the Das Velhas River Basin

Abstract: In the management of water resources, it is necessary to balance the demands of multiple uses of water and water availability, while enabling use in an environmentally sustainable way. Probability distributions of flow rates are essential tools for assessing water availability. The objectives of this work were to analyze the best probability distribution that conforms to the annual minimum daily average discharge for periods of seven consecutive days (Q7) for 14 stream gauging stations in the Das Velhas River … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
0
0
4
Order By: Relevance
“…It was found that the Weibull, LogPearson 3 and Pearson 3 distributions were the ones that presented the lowest standard errors, 0.87, 0.90 and 0.94 m³.s -1 respectively, therefore the best fit, while the distributions that presented the highest standard errors were the LogNormal 3 and 2 parameter distributions, 1.02 and 1.12 m³.s -1 respectively.In a research carried out by Zoneamento Ecológico-Econômico de Minas Gerais (Minas Gerais, 2008), it was found a value of 29.28 m³.s -1 for low flow rate Q7,10, with a relative error of 27.01% for the same fluviometric station of this study. In addiction,Melo et al (2019) found values close to Q7,10 for fluviometric station of Jequitibá River (MG), 23.60 m³.s -1, which has a drainage area similar to that of Rio das Mortes basin.…”
mentioning
confidence: 61%
“…It was found that the Weibull, LogPearson 3 and Pearson 3 distributions were the ones that presented the lowest standard errors, 0.87, 0.90 and 0.94 m³.s -1 respectively, therefore the best fit, while the distributions that presented the highest standard errors were the LogNormal 3 and 2 parameter distributions, 1.02 and 1.12 m³.s -1 respectively.In a research carried out by Zoneamento Ecológico-Econômico de Minas Gerais (Minas Gerais, 2008), it was found a value of 29.28 m³.s -1 for low flow rate Q7,10, with a relative error of 27.01% for the same fluviometric station of this study. In addiction,Melo et al (2019) found values close to Q7,10 for fluviometric station of Jequitibá River (MG), 23.60 m³.s -1, which has a drainage area similar to that of Rio das Mortes basin.…”
mentioning
confidence: 61%
“…Em contrapartida, Minuzzi e Caramori (2011) não detectaram mudanças significativas no comportamento da chuva no estado do Paraná, apesar das descontinuidades notadas nas décadas de 1980 e 1990 para chuvas sazonais e anuais em alguns postos. Outros estudos também relatam a inexistência de tendência em séries temporais de precipitação em outras regiões do país, o que evidencia a heterogeneidade climática brasileira e a cautela necessária em análises mais abrangentes (Marengo e Alves, 2005;Alexandre et al, 2010;Blain, 2010;Lima et al, 2011;Nunes et al 2018;Penereiro e Meschiatti, 2018;Alcântara et al, 2019;Melo et al, 2019).…”
Section: Período Analisadounclassified
“…Na bacia do rio Paraíba do Sul, Marengo e Alves ( 2005) relatam a estacionariedade da série de precipitação e a tendência de decréscimo das vazões, o que foi atribuído à interferência antrópica na bacia. Na mesma linha, Melo et al (2019) detectaram tendência de diminuição das vazões mínimas de sete dias de duração em três estações fluviométricas na bacia do rio das Velhas, Minas Gerais, embora não tenha sido constatada qualquer tendência nas séries de precipitação na região.…”
Section: Período De Análiseunclassified
See 2 more Smart Citations